Spontaneous emulsification. (April 2016) - Solans, Conxita; Morales, Daniel; Homs, Maria
Abstract: Spontaneous emulsification may occur when immiscible liquids in non-equilibrium conditions are in contact. This phenomenon is triggered by gradients of chemical potential between the phases, which under certain conditions lead to negative values of free energy of emulsification. A summary of background information on spontaneous emulsification is first presented with emphasis on proposed mechanisms. It follows a description of recent developments, in both surfactant-free and surfactant systems. Applications based on the use of spontaneous emulsification to produce delivery systems and nanostructured materials with improved properties in a cost-effective way are also described. Graphical abstract: Schematic Gibbs free energy profile of emulsification processes driven by the internal energy of the system Highlights: Mechanisms of spontaneous emulsification were summarized. Metastable (ouzo effect) emulsions in water/co-solvent/oil systems were described. The key role of intermediate phases in systems with surfactants undergoing spontaneous emulsification was discussed. Applications of spontaneous emulsification in diverse fields were described.